Advances in the Management of Meconium Aspiration Syndrome - Kamala Swarnam; Amuchou S. Soraisham; Sindhu Sivanandan (International Journal of Pediatrics)
Meconium aspiration syndrome (MAS) is a common cause of severe respiratory distress in term infants, with an associated highly variable morbidity and mortality. MAS results from aspiration of meconium during intrauterine gasping or during the first few breaths. The pathophysiology of MAS is multifactorial and includes acute airway obstruction, surfactant dysfunction or inactivation, chemical pneumonitis with release of vasoconstrictive and inflammatory mediators, and persistent pulmonary hypertension of newborn (PPHN). This disorder can be life threatening, often complicated by respiratory failure, pulmonary air leaks, and PPHN. Approaches to the prevention of MAS have changed over time with collaboration between obstetricians and pediatricians forming the foundations for care. The use of surfactant and inhaled nitric oxide (iNO) has led to the decreased mortality and the need for extracorporeal membrane oxygenation (ECMO) use. In this paper, we review the current understanding of the pathophysiology and management of MAS.